2018
DOI: 10.1103/physreva.98.023624
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional splitting dynamics of giant vortices in Bose-Einstein condensates

Abstract: We study the splitting dynamics of giant vortices in dilute Bose-Einstein condensates by numerically integrating the three-dimensional Gross-Pitaevskii equation in time. By taking advantage of tetrahedral tiling in the spatial discretization, we decrease the error and increase the reliability of the numerical method. An extensive survey of vortex splitting symmetries is presented for different aspect ratios of the harmonic trapping potential. The symmetries of the splitting patterns observed in the simulated d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…State-of-the-art BEC experiments enable us to routinely create [20,21] such topological structures and inspect their equilibria [22][23][24] and dynamical properties [25][26][27][28] with an unprecedented level of accuracy [29][30][31]. Moreover, a multitude of studies have focused on the creation of multiple vortices of the same [31,32] or of opposite charges [33,34], vortices of higher topological charge [35][36][37][38] and the associated dynamical instabilities of these topological objects [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…State-of-the-art BEC experiments enable us to routinely create [20,21] such topological structures and inspect their equilibria [22][23][24] and dynamical properties [25][26][27][28] with an unprecedented level of accuracy [29][30][31]. Moreover, a multitude of studies have focused on the creation of multiple vortices of the same [31,32] or of opposite charges [33,34], vortices of higher topological charge [35][36][37][38] and the associated dynamical instabilities of these topological objects [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Each of these exotic splitting modes is the dominant dynamical instability of the respective stationary vortex in a wide range of intercomponent interaction strengths and relative populations of the two condensate components and should be amenable to experimental detection. Our results contribute to a better understanding of vortex physics, hydrodynamic instabilities, and two-dimensional quantum turbulence in multicomponent superfluids.The aforementioned studies of vortex splitting [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] were conducted for a solitary scalar BEC, which is described by a single C-valued order parameter. However, vortex physics becomes much more diverse when multiple, say K ∈ N, scalar condensates come into contact, interact with one another, and thereby constitute an K-component BEC described by a C K -valued vectorial order parameter.…”
mentioning
confidence: 99%
“…We stress that to achieve the stable results for the dynamics of DQV produced in the ringshaped BEC, our calculation in the r, φ, z space is much less time-consuming than the one in the x, y, z space, e.g., at least five times less than the calculation time in the Cartesian coordinate system for one dynamics process. To decrease the error induced by the square lattice in the dynamics of giant vortices, the latest work employs discrete exterior calculus with tetrahedral tiling [13]. To get first insight, and see the stability of a DQV, we begin by discussing the oscillation of the ring-shaped BEC with the symmetric density envelope in an isotropic trap, i.e., η = 0.…”
Section: Simulation Schemes and Numerical Methodsmentioning
confidence: 99%
“…Therefore, it will be a challenge and interesting issue to create a stable multiply quantized vortex with relatively long lifetime and investigate some complex dynamics associated with such quantum circulation in a controllable way. It is shown that a stable giant vortex may be realized in condensates with a localized pinning potential [11], in a quartic potential [12], or oblate condensates [13]. In harmonically * yangt@nwu.edu.cn trapped three-dimensional (3D) condensates the stability of a giant vortex depends strongly on the trap anisotropy and the strength of interatomic interaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation